Neonatal administration of fluoxetine did not alter the anxiety indicators, but decreased the locomotor activity in adult rats in the elevated plus-maze Administração neonatal de fluoxetina não alterou os indicadores de ansiedade, mas diminuiu a atividade locomotora em ratos adultos no labirinto elevado em cruz - Valdenilson Ribeiro Ribas; Helena Karine Rufino Aniceto; Hugo André de Lima Martins; Ketlin Helenise dos Santos Ribas; Renata de Melo Guerra-Ribas; Simone do Nascimento Fraga; Valéria Ribeiro-Ribas; Célia Maria Mendes Vasconcelos; Marcelo Tavares Viana; Raul Manhaes-de-Castro (Arquivos de Neuro-Psiquiatria)
The objective of this study was evaluate the anxiety and locomotor activity (LA) in 52 Wistar adult male rats, being 26 treated with fluoxetine (10 mg/Kg - sc) in the neonatal period. These same rats received foot shock (FS) (1.6-mA - 2-s) in the 90th day. The anxiety and LA were appraised by plus-maze. The time spent in the open arms was used as anxiety index and the LA was measured by number of entries in closed arms (NECA) and the total of entries (TE). T-test was used with p<0.05 and expresses data in mean±SEM. There were reductions with the fluoxetine group in the NECA (2.35±0.33) and in the TE (3.96±0.61) compared to the controls (4.65±0.52) and (6.96±0.94). The neonatal administration of fluoxetine did not alter the anxiety, but reduced the LA in the animals that received FS. O objetivo deste estudo foi avaliar a ansiedade e a atividade locomotora (AL) em 52 ratos Wistar adultos machos, sendo 26 tratados no período neonatal com fluoxetina (10 mg/Kg - sc) e no 90º dia, receberam estímulos elétricos nas patas (1,6-mA-2-s). A ansiedade e a AL foram avaliadas por meio do labirinto elevado em cruz. O tempo de permanência dos animais nos braços abertos (BA) foi utilizado como índice de ansiedade e a AL medida pelo número de entradas nos braços fechados (NEBF) e pelo total de entradas (TE) nos BA e BF. O teste t foi utilizado, com (p<0,05) e os dados apresentados em média±erro padrão. Os animais tratados reduziram o NEBF (2,35±0,33) e o TE (3,96±0,61) comparados a seus controles (4,65±0,52) e (6,96±0,94). A administração neonatal de fluoxetina não alterou a ansiedade, mas diminuiu a AL dos animais que receberam EE.